Políticas sociales, cuerpos y emociones a principios del siglo XIX en Argentina - Rebeca Beatriz Cena (Universidad Autónoma del Estado de México, 2015)
In this paper I will discuss from an approach that recovers the sociolog y of the body and emotions the first actions in the field of social policy in Argentina in the early nineteenth century, conducted by the Charitable Society of the Capital. From a qualitative analysis of secondary data, I will discuss the impact that government intervention possesses in terms of certain assumptions related to how the beneficiaries of social policies should behave. It is concluded that governmental interventions together with the regime of capitalist accumulation presuppose a set of emotions and sensitivities related to living in an abject deprivation condition.